2022
DOI: 10.3390/mi13050710
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Grinding Force and Material Removal Mechanism of Laser-Structured Zirconia Ceramics

Abstract: Zirconia is a high demanded structural ceramic with desirable mechanical, thermal, and chemical properties. Poor surface integrity and limited material removal rate caused by high cutting force and wheel wear are the main problems in ceramic grinding. In order to reduce the grinding force and enhance the removal rate in grinding, zirconia ceramics are firstly ablated by laser and then be grinded. A nanosecond laser is used to ablate the surface of zirconia ceramic, the laser-ablated structures with micro pits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In contrast to laser preheating-assisted grinding, which alters the thermophysical properties of materials to enhance processing efficiency [26], some researchers have explored laser surface texturing as a means to improve material removal efficiency by altering the physical properties of the material. Pang et al conducted surface texturing on zirconia ceramics and confirmed the improved grinding performance achieved through this approach [27]. Azarhoushang et al developed a novel laser-assisted grinding process to achieve a damage-free grinding surface with the assistance of laser technology [28].…”
Section: Introductionmentioning
confidence: 96%
“…In contrast to laser preheating-assisted grinding, which alters the thermophysical properties of materials to enhance processing efficiency [26], some researchers have explored laser surface texturing as a means to improve material removal efficiency by altering the physical properties of the material. Pang et al conducted surface texturing on zirconia ceramics and confirmed the improved grinding performance achieved through this approach [27]. Azarhoushang et al developed a novel laser-assisted grinding process to achieve a damage-free grinding surface with the assistance of laser technology [28].…”
Section: Introductionmentioning
confidence: 96%
“…At present, the research work on improving the surface machining quality of Si 3 N 4 ceramic materials mainly focuses on the grinding mechanism of ceramic materials, the micro morphology of ceramic surface and the core key technologies such as diamond grinding wheel dressing. Representative research work includes literature [3][4][5][6][7], which discusses the influence of different grinding processes on the surface roughness, surface morphology and sub-surface damage of Si 3 N 4 based on the brittle fracture characteristics of Si 3 N 4 materials in the traditional grinding process. At the same time, it is consistently proposed that the process from brittle removal to plastic removal in Si 3 N 4 grinding can obviously improve the grinding surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported a maximum of 40% reduction in grinding forces. 29 According to the abovementioned discussions, several researches have investigated the effect of macro-micro-structures on the outputs of the grinding process. However, in previous researches, the material removal volume by laser structuring was not constant for different patterns.…”
Section: Introductionmentioning
confidence: 99%